Validation of scaffold design optimization in bone tissue engineering: finite element modeling versus designed experiments. (21st February 2017) - Uth, Nicholas; Mueller, Jens; Smucker, Byran; Yousefi, Azizeh-Mitra
Abstract: This study reports the development of biological/synthetic scaffolds for bone tissue engineering (TE) via 3D bioplotting. These scaffolds were composed of poly(L-lactic-co-glycolic acid) (PLGA), type I collagen, and nano-hydroxyapatite (nHA) in an attempt to mimic the extracellular matrix of bone. The solvent used for processing the scaffolds was 1, 1, 1, 3, 3, 3-hexafluoro-2-propanol. The produced scaffolds were characterized by scanning electron microscopy, microcomputed tomography, thermogravimetric analysis, and unconfined compression test. This study also sought to validate the use of finite-element optimization in COMSOL Multiphysics for scaffold design. Scaffold topology was simplified to three factors: nHA content, strand diameter, and strand spacing. These factors affect the ability of the scaffold to bear mechanical loads and how porous the structure can be. Twenty four scaffolds were constructed according to an I-optimal, split-plot designed experiment (DE) in order to generate experimental models of the factor-response relationships. Within the design region, the DE and COMSOL models agreed in their recommended optimal nHA (30%) and strand diameter (460 μ m). However, the two methods disagreed by more than 30% in strand spacing (908 μ m for DE; 601 μ m for COMSOL). Seven scaffolds were 3D-bioplotted to validate the predictions of DE and COMSOL models (4.5–9.9 MPa measured moduli). The predictions for these scaffolds showed relative agreement for scaffold porosity (mean absolute percentage error of 4% for DE and 13% for COMSOL), but were substantially poorer for scaffold modulus (51% for DE; 21% for COMSOL), partly due to some simplifying assumptions made by the models. Expanding the design region in future experiments (e.g., higher nHA content and strand diameter), developing an efficient solvent evaporation method, and exerting a greater control over layer overlap could allow developing PLGA-nHA-collagen scaffolds to meet the mechanical requirements for bone TE.